Cancer survival among Alaska Native people. Issue 12 (26th March 2018) - Nash, Sarah H.; Meisner, Angela L. W.; Zimpelman, Garrett L.; Barry, Marc; Wiggins, Charles L.
Abstract : BACKGROUND: Recent cancer survival trends among American Indian and Alaska Native (AN) people are not well understood; survival has not been reported among AN people since 2001. METHODS: This study examined cause‐specific survival among AN cancer patients for lung, colorectal, female breast, prostate, and kidney cancers. It evaluated whether survival differed between cancers diagnosed in 1992‐2002 (the earlier period) and cancers diagnosed in 2003‐2013 (the later period) and by the age at diagnosis (<65 vs ≥65 years), stage at diagnosis (local or regional/distant/unknown), and sex. Kaplan‐Meier and Cox proportional hazards models were used to estimate univariate and multivariate‐adjusted cause‐specific survival for each cancer. RESULTS: An improvement was observed in 5‐year survival over time from lung cancer (hazard ratio [HR] for the later period vs the earlier period, 0.83; 95% confidence interval [CI], 0.72‐0.97), and a marginally nonsignificant improvement was observed for colorectal cancer (HR, 0.81; 95% CI, 0.66‐1.01). Site‐specific differences in survival were observed by age and stage at diagnosis. CONCLUSIONS: This study presents the first data on cancer survival among AN people in almost 2 decades. During this time, AN people have experienced improvements in survival from lung and colorectal cancers. The reasons for these improvements may include increased access to care (including screening) as well as improvements in treatment. Improving cancer survival should be a priority for reducing the burden of cancer among AN people and eliminating cancer disparities. Cancer 2018;124:2570‐7 . © 2018 American Cancer Society . Abstract : This study presents the first data on selected cancer survival among Alaska Native people in almost 2 decades. During this time, Alaska Native people have experienced improvements in survival from lung and colorectal cancers, but survival from breast, prostate, and kidney cancers has not changed.